Transcervical Endoscopic Esophageal Mobilization: An Approach to Transhiatal Esophagectomy - Jennifer Livschitz, MD, MS; Joshua Melamed, MD; Britton Donato, MD; Amy Yoonjin Lee, MD; Huaying Dong, BS; Aniko Szabo, PhD; William B. Tisol, MD; Paul L. Linsky, MD; Mario G. Gasparri, MD; David W. Johnstone, MD (Annals of Thoracic Surgery Short Reports)
Background: Transcervical endoscopic esophageal mobilization (TEEM) is an approach to transhiatal esophagectomy that aims to minimize blood loss and decrease the operative time commonly associated with traditional transhiatal technique. Methods: A retrospective chart review was conducted on patients who underwent TEEM esophagectomy between 2009 and 2020. Baseline characteristics, perioperative outcomes, and postoperative complications were recorded. To report survival, a Kaplan-Meier survival plot was developed using SAS software (SAS Institute). Results: A total of 241 patients underwent TEEM esophagectomy. The mean operative time was 185.1 ± 59.3 minutes, blood loss was 251.4 ± 212.3 mL, the number lymph nodes dissected was 13.6 ± 6.2, and the length of stay was 11.9 ± 8.5 days. In the postoperative setting, 68 (28.2%) patients experienced hoarseness, 62 (25.7%) had postoperative atrial fibrillation, 30 (12.4%) had an anastomotic leak, and 12 (4.6%) experienced chylothorax. The overall 30- and 90-day mortality rates were 2.1% (5 of 241) and 4.6% (11 of 241), respectively. The median overall survival was 2.36 years, with 60% 3-year survival and 40% 5-year survival. Conclusions: TEEM esophagectomy is a safe approach with acceptable postoperative morbidity and mortality and shorter operative times compared with historical norms.